RIFM fragrance ingredient safety assessment, 3-Cyclohexene-1-carboxaldehyde, 1-ethenyl-, CAS Registry Number 1049017-63-1. (September 2022) - Api, A.M.; Belsito, D.; Botelho, D.; Bruze, M.; Burton, G.A.; Cancellieri, M.A.; Chon, H.; Dagli, M.L.; Date, M.; Dekant, W.; Deodhar, C.; Fryer, A.D.; et al.
Abstract: The existing information supports the use of this material as described in this safety assessment . 3-Cyclohexene-1-carboxaldehyde, 1-ethenyl- was evaluated for genotoxicity, repeated dose toxicity, reproductive toxicity, local respiratory toxicity, phototoxicity/photoallergenicity, skin sensitization, and environmental safety. Data show that 3-cyclohexene-1-carboxaldehyde, 1-ethenyl- is not genotoxic. Data on 3-cyclohexene-1-carboxaldehyde, 1-ethenyl- provide a calculated Margin of Exposure (MOE) > 100 for the repeated dose toxicity endpoint. The reproductive and local respiratory toxicity endpoints were evaluated using the Threshold of Toxicological Concern (TTC) for a Cramer Class I material, and the exposure to 3-cyclohexene-1-carboxaldehyde, 1-ethenyl-is below the TTC (0.03 mg/kg/day and 1.4 mg/day, respectively). Data provided 3-cyclohexene-1-carboxaldehyde, 1-ethenyl- a No Expected Sensitization Induction Level (NESIL) of 1000 μg/cm 2 for the skin sensitization endpoint. The phototoxicity/photoallergenicity endpoints were evaluated based on ultraviolet/visible (UV/Vis) spectra; 3-cyclohexene-1-carboxaldehyde, 1-ethenyl- is not expected to be phototoxic/photoallergenic. The environmental endpoints were evaluated; 3-cyclohexene-1-carboxaldehyde, 1-ethenyl- was found not to be Persistent, Bioaccumulative, and Toxic (PBT) as per the International Fragrance Association (IFRA) Environmental Standards, and its risk quotients, based on its current volume of use in Europe and North America (i.e., Predicted Environmental Concentration/Predicted No Effect Concentration [PEC/PNEC]), are <1. Highlights: 3-Cyclohexene-1-carboxaldehyde, 1-ethenyl-; a safety assessment based on RIFM's criteria. A safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data, read-across, and/or TTC.